2018
DOI: 10.3389/fphys.2018.00030
|View full text |Cite
|
Sign up to set email alerts
|

Invertebrate Trehalose-6-Phosphate Synthase Gene: Genetic Architecture, Biochemistry, Physiological Function, and Potential Applications

Abstract: The non-reducing disaccharide trehalose is widely distributed among various organisms. It plays a crucial role as an instant source of energy, being the major blood sugar in insects. In addition, it helps countering abiotic stresses. Trehalose synthesis in insects and other invertebrates is thought to occur via the trehalose-6-phosphate synthase (TPS) and trehalose-6-phosphate phosphatase (TPP) pathways. In many insects, the TPP gene has not been identified, whereas multiple TPS genes that encode proteins harb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 110 publications
1
64
0
Order By: Relevance
“…The insect fat body is an important place for trehalose synthesis, like the liver in mammals (Candy and Kilby, 1959;Murphy and Wyatt, 1965;Friedman, 1968;Tang et al, 2018). Therefore, many studies have found that TPS mRNA expression can be detected in fat bodies (Cui and Xia, 2009;Xu et al, 2009;Chen et al, 2010;Tang et al, 2010;Xiong et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The insect fat body is an important place for trehalose synthesis, like the liver in mammals (Candy and Kilby, 1959;Murphy and Wyatt, 1965;Friedman, 1968;Tang et al, 2018). Therefore, many studies have found that TPS mRNA expression can be detected in fat bodies (Cui and Xia, 2009;Xu et al, 2009;Chen et al, 2010;Tang et al, 2010;Xiong et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In the adipose tissue, ADSCs represent a fraction of the entire resident population, that can undergo differentiation under specific external stimuli [ 26 ]. In the niche in which they reside, ADSCs are responsible for maintaining adipose tissue physiology and its renewal [ 27 ]. Moreover, in recent years, different kind of isolation procedures of these cells from the stromal vascular fraction (SVF) have been optimized in order to easily obtain a high yield of stem cells with a higher differentiation potential, as compared to stem cells from other sources [ 25 , 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the group of cellular carbohydrate metabolism of S. leurokolos, more than 60% of genes were annotated as TPSs, which were key enzymes for trehalose biosynthesis. Trehalose, a non-reducing disaccharide, is a multifunctional molecule that plays important roles in sugar metabolism, stress recovery, chitin synthesis and other biological processes [44]. Trehalose is also a protectant responsible for thermotolerance, as demonstrated in Saccharomyces cerevisiae [45].…”
Section: Discussionmentioning
confidence: 99%